2017
DOI: 10.1016/j.nuclphysa.2016.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Classical electromagnetic fields from quantum sources in heavy-ion collisions

Abstract: Electromagnetic fields are generated in high energy nuclear collisions by spectator valence protons. These fields are traditionally computed by integrating the Maxwell equations with point sources. One might expect that such an approach is valid at distances much larger than the proton size and thus such a classical approach should work well for almost the entire interaction region in the case of heavy nuclei. We argue that, in fact, the contrary is true: due to the quantum diffusion of the proton wave functio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…Our paper paves the road to a comprehensive computation of electromagnetic field with quantum sources, whose importance was demonstrated in [56,57]. The fact that the flow of plasma and the wake effects are but small corrections is enormous simplification of the MHD equations.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Our paper paves the road to a comprehensive computation of electromagnetic field with quantum sources, whose importance was demonstrated in [56,57]. The fact that the flow of plasma and the wake effects are but small corrections is enormous simplification of the MHD equations.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, for our arguments in this paper it is sufficient to approximate the valence electric charges as classical point particles. In a more comprehensive treatment one has to replace the classical sources by the quantum distributions [56,57].…”
mentioning
confidence: 99%
“…A number of numerical simulations have revealed that the magnitudes of the magnetic fields in heavy-ion collisions can be very large [5][6][7][8][9][10][11][12][13][14][15][16]. In Fig.…”
Section: A Numerical Approachmentioning
confidence: 99%
“…Unfortunately, it is very difficult to assess the precise magnitude of the magnetic fields relevant to this situation, and the question is currently under intense scrutiny. The maximal possible values of eB, those attained in the initial state of the fireball generated by a peripheral collision, were estimated in the classic work of Deng et al [21], but it has recently been suggested that these values may need to be reconsidered: in [22,23], for example, it is argued that quantum diffusion effects can significantly adjust the estimated initial magnetic field upward.…”
Section: Peripheral Lhc Vs Central Rhicmentioning
confidence: 99%